INTERNALISASI GURU DALAM MENANAMKAN NILAI KEDISIPLINAN MELALUI METODE KEPEMIMPINAN DI PAUD - Salsabila Arkana Kusumasanti (CV. Adiba Aisha Amira, 2026)
Early Childhood Education (PAUD) is a form of education that emphasizes the formation of a child's personality from an early age. The early childhood period, particularly between 0 and 6 years, is often known as the